Characteristic and categorization of monoprint’s among local artists in Malaysia / Muhammad Abdullah ... [et al.] - Muhammad, Abdullah; Mohd Firdaus Naif, Omran Zailuddin; Ahmad Khairul Azizi, Ahmad; Mohd Nasiruddin, Abdul Aziz; Ashraf, Abdul Rahaman (Universiti Teknologi MARA, Perak, 2020)
Monoprint is part of the technique that well established in printmaking. The characteristic and categorization of monoprint is easily recognized as a single output and different with the edition that usually created through other medium such as silkscreen, etching, engraving and others. Based from the current and previous studies that related with characteristic and categorization of monoprint, which created by local visual artists in Malaysia need more further detail information and introduction compared to the other develop countries that were established their monoprint medium. Therefore, the objective of this research is to study characteristic of monoprint artwork that explore by printmaker artists in Malaysia and to categorize the selected artworks, in order to recognize the monoprint artwork through their characteristic. This study will begin by selected artworks that show the specific monoprint characteristic that explore by printmaker artists in Malaysia. This study will be conducted by several of monoprint characteristic and categorization from experts. The results of the assessment there were 11 categorizations from two main monoprint characteristic which is creative expression and innovation technique. This study will deliver a proper instruction, guideline, knowledge, and differentiate in between edition and single expression through monoprint. This study has shown that local artist consists of different background and that local artists tried to come out with new approach and dimension in produced monoprint artworks in Malaysia